Eu-Tb-Doped Y-BTC MOF: A Step Towards Optimization of an Energy Conversion System - Francesca Lo Presti; Anna Lucia Pellegrino; Francesca Loschi; Emil Milan; Adolfo Speghini; Graziella Malandrino (Crystals)
Lanthanide-based metal–organic frameworks (Ln-MOFs) represent a key material in various optical applications. Thus, they offer the possibility of fine-tuning their functional properties by adjusting the composition, stoichiometry, and ligand nature. This work reports for the first time the environmentally friendly one-pot synthesis of Eu-Tb-doped yttrium-1,3,5-benzenetricarboxylate MOF, i.e., Y-BTC: Eu (10%), Tb (10%), under mild conditions of temperature and pressure. Structural and morphological investigations were conducted through ATR-IR, XRD, and FE-SEM characterization. The doping percentage was analyzed by EDX spectroscopy. The luminescence properties confirm the down-shifting behavior of the MOF, paving the way for using this Eu-Tb-doped Y-BTC system in photovoltaic technology.